News Aggregator dan Nilai-Nilai Jurnalisme: Studi Penyajian Berita Pada Beritagar.Id - Alfito Deannova Ginting; Rifa Aisatu Ulfa Zaini; Anna Agustina; Selvi Septiani (CoverAge: Journal of Strategic Communication, 2019)
News aggregator is a new profession that emerges along with the abundance of information. This article aims to analyze the results of the work practices of the news aggregator whose roles are mostly held by journalists in Indonesia. The news aggregators who also work as journalists, have professional ethics guidelines in the corridor of the journalistic process where the journalistic code of ethics must be implemented, the elements of journalism need to be carried out, as well as the composition of news with information in accordance with 5W1H. This guideline becomes the concept of analyzing news content which in this study is focused on news content in beritagar.id. The results showed that the news aggregation office, in this case beritagar.id, ran a journalistic process according to journalism values. However, it is still not recognized as journalism since the principle of going to the field to collect data directly is important in the process of verifying journalistic product data. Interestingly, the results of this study indicate an increase in understanding of the journalistic process in media aggregators for senior journalists who began their careers in the mainstream media.